Supplementary corpora lutea monitoring allows progestin treatment interruption on day 70 of pregnancy in non-cyclic recipient mares - Silva, E. S. M. [UNESP]; Frade, S. C. F.; Ignacio, F. S. [UNESP]; Pantoja, José Carlos de Figueiredo [UNESP]; Puoli Filho, J. N. P. [UNESP]; Meira, Cezinande de [UNESP] (Elsevier B.V., 2014)
The present study evaluated the effect of altrenogest treatment during 70 or 120 days of gestation on pregnancy maintenance in non-cyclic recipient mares and correlated the hormonal interruption findings with number, supplementary corpora lutea (SCL) formation period, and plasma progesterone (P4). Twenty five mares were used as recipients during anestrus, transitional or ovulatory phase and were assigned into groups according to altrenogest treatment period (70ALT, 120ALT or Control groups) or reproductive status at beginning of treatment (Anestrus, Transition or Cyclic/Control groups). Mares were evaluated by ultrasonography and quantification of plasma progesterone to monitor pregnancy status, SCL formation and P4 profile. After hormonal withdrawal, abortion was only observed on group 70ALT. The days of first SCL formation were similar (p = 0.32) in the 70ALT and 120ALT groups and greater (p < 0.01) than the Control group. In addition, the first SCL formation period occurred later during gestation in the anestrus group than in the transitional or cyclic mares. Progesterone synthesis in non-cyclic mares occurred in more advanced gestational period and showed lower concentration during the 120 days in relation to cyclic mares. It is suggested that progestin treatment interruption in non-cyclic recipient mares at 70 days of gestation allows pregnancy maintenance when SCL are observed and at 120 days enables maintenance in all recipient mares. In addition, the first SCL development period occurs in different gestational phases during pregnancy among anestrus, transitional and cyclic mares. This study improves the understanding of pregnancy physiology and enables progestins treatment interruption on day 70 of pregnancy in non-cyclic pregnant recipient mares. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Altrenogest; Non-cyclic mares; Supplementary corpora lutea; Progesterone